USING ROLE PLAYING METHOD TO IMPROVE STUDENTS SPEAKING SKILLS AT SMP MARISI MEDAN - Lita K Sihombing; Riana Pangaribuan; Sri Ninta Tarigan; Imelda M Simorangkir (ELT (English Language Teaching Prima Journal), 2022)
One of the skills that must be mastered in learning English is speaking. But many peopledo not have the confidence to speak English because of some problems suchaspronunciation, and vocabulary. One method that can improve students' speakingskillsisthe role-playing method. This study aims to determine the application of the role-playingmethod in improving students' speaking skills in speaking English in class IXSMPMarisi Medan. Researchers used the roleplaying method to improve students' speakingskills. The author uses quantitative research. The research subjects were gradeIXstudents. The author took one class used in the study consisting of 38 students. Afterusing the role-playing method, students can improve their speaking skills. This increasecan be seen from the results of observations and practice. Data collection techniquesusing documentation, questionnaires, and observations. The results of data processingshowed an increase in students' speaking ability which was applied by the role-playingmethod. This is evident from the results of the questionnaire. The overall resultsofrespondents' answers obtained strongly disagree as much as 43.9 %, disagreeasmuchas 161.4%, agree as much as 409.4%, and strongly agree 397.5%. Based on theresultsof this study, it can be concluded that the use of the Role Playing method canimprovestudents' speaking skills in English lessons. Based on the results of the study, therearesuggestions to be conveyed to teachers who will conduct English learning toconsiderthe use of learning methods, such as the Role Playing method which has beenproventoimprove students' speaking skills. Keywords : speaking skills, role playing